2013
DOI: 10.1037/a0028418
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating religiosity into a developmental model of positive family functioning across generations.

Abstract: This study evaluated a developmental model of intergenerational continuity in religiosity and its association with observed competency in romantic and parent-child relationships across two generations. Using multi-informant data from the Family Transitions Project, a 20-year longitudinal study of families that began during early adolescence (N = 451), we found that parental religiosity assessed during the youth’s adolescence was positively related to the youth’s own religiosity during adolescence which, in tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 87 publications
3
36
0
1
Order By: Relevance
“…These results are consistent with meta-analytic reviews of the literature by others (Mahoney et al, 2001) and by more recent research published in this field (Spilman et al, 2013;David and Staffor, 2013). Among studies with the best methodology (ratings of 7 or higher), 35 of 38 studies reported this finding.…”
Section: Marital Stabilitysupporting
confidence: 90%
“…These results are consistent with meta-analytic reviews of the literature by others (Mahoney et al, 2001) and by more recent research published in this field (Spilman et al, 2013;David and Staffor, 2013). Among studies with the best methodology (ratings of 7 or higher), 35 of 38 studies reported this finding.…”
Section: Marital Stabilitysupporting
confidence: 90%
“…In turn, positive parenting may reduce the later risk of unemployment in the offspring (Kokko & Pulkkinen 2000) and appears to be implicated in the intergenerational transmission of social competence and romantic relationship quality (Ehrensaft, Knous-Westfall, & Cohen 2011). Moreover, religiosity, which was shown to predict positive parenting (Spilman, Neppl, Donnellan, Schofield, & Conger 2013), is also a major predictor of civic engagement, especially volunteering, because religious people are often embedded in church communities that espouse helping values and actively recruit volunteers (Verba et al 1995;Wilson 2000).…”
Section: The Present Studymentioning
confidence: 99%
“…Many religious parents desire to pass their own religious beliefs, practices, and commitments on to their children. Indeed, intergenerational transmission of religious belief is a well-established part of family studies (Bengtson et al 2013;Spilman et al 2013). Given the American penchant for change, including religious change, perhaps it is also not surprising that a 2009 study conducted by the Pew Research Center found that 44% of Americans reported that they had left the religious affiliation of their childhood (Pew Research Center 2009).…”
Section: Introductionmentioning
confidence: 99%